A common novel splice variant of SLC22A1 (OCT1) is associated with impaired responses to imatinib in patients with chronic myeloid leukaemia. (10th October 2013) - Grinfeld, Jacob; Gerrard, Gareth; Alikian, Mary; Alonso‐Dominguez, Juan; Ale, Sakuntala; Valgañon, Mikel; Nteliopoulos, Georgios; White, Deborah; Marin, David; Hedgley, Corinne; O'Brien, Stephen; Clark, Richard; et al.
Summary Approximately one‐third of patients with chronic myeloid leukaemia will fail to achieve or maintain responses to imatinib. Changes in solute carrier family 22 (organic cation transporter), member 1 (SLC22A1, also termed OCT1), the main transporter for imatinib, have been proposed as a possible predictive factor. We analysed SLC22A1 mRNA levels and single nucleotide polymorphisms (SNPs) located in exon 7 in 153 diagnostic whole blood samples from two patient cohorts. The level of SLC22A1 expression did not significantly correlate with imatinib failure or achievement of molecular remission. The SNP 408V>M (g.1222G>A) was present in 65% of patients and was associated in all cases with an eight base‐pair insertion (8+ allele) at the 3′ end of exon 7. The latter generates an alternative splice site, leading to a premature stop codon. M420del was found in 33% of patients and never in cis with 8+ (the 3− allele). Significantly longer times to 1% and 0·1% molecular responses (by quantitative reverse transcription polymerase chain reaction) were seen in patients with 8+8+ or 8+N compared to those with the remaining four genotypes (N = no insertion or deletion). Patients lacking 8+ and 3− (NN, 18%) showed the best outcomes overall. Thus, while SLC22A1 expression does not appear to affect response, alterations in its splicing or amino acid sequence may do so.